Exploring the role of digital media dependency on the relationship between personal involvement and flashbulb memory during the pandemic: Empirical evidence from Mainland China - Ma, Xiaoyue; Wan, Jing (Frontiers in Psychology, 2022)
Flashbulb memory (FBM) is viewed as a special type of autobiographical memory due to its richness of individuals’ self-related details when hearing the news and the long duration. It also helps shape people's impression of public events to some extent. Given that personal involvement is one of the important antecedent variables of FBM, this study proposed to investigate it from spatiotemporal involvement (spatiotemporal distance) and empathic involvement (empathy level) to explore the impact of personal involvement on the formation of FBM during the Covid-19 pandemic. In particular, digital media dependency was considered in the influence of involvement on the FBM since it is a crucial information source for individuals and a path to spread information about their lives and work during the pandemic. In this study, a total of 546 valid questionnaires (from May 1, 2022, to May 7, 2022) and 349 valid questionnaires (from May 10, 2022, to May 17, 2022) were collected through a two-stage online survey in Shanghai, China towards the epidemic wave at the end of March 2022. The mediating mode of digital media dependency was also examined on personal involvement in FBM performance, which consists of FBM specificity, confidence, and consistency. Results showed that empathic involvement had a significant negative influence on FBM specificity, namely the higher the empathy level was, the worse the FBM specificity would be, in which digital media dependency played a suppressing effect. Individuals’ spatiotemporal involvement was proved to have a significant positive influence on FBM specificity and consistency. It was one of the first to investigate the FBM formation process around "small peak" events in the context of the ongoing pandemic. Innovatively, empathy was adopted as the index of memory arousal for empathic involvement, and digital media dependency was considered an important mediator variable in the memory study. The research results have practical significance for promoting the process of epidemic recovery integrated with digital media and can provide a social reference for the shaping process of disaster memory from the perspective of digital information and emotional transmission.